The effects of aerator masks and medical masks on oxygen saturation (SO2) on mentally retarded athletes - Singgih Hendarto; Rumi Iqbal Doewes; Sapta Kunta Purnama; Islahuzzaman Nuryadin; Manshuralhudlori Manshuralhudlori (AOSIS, 2022)
The study purpose was investigated the effect of aerator masks on the oxygen saturation (SO2) of mentally retarded athletes compared to medical masks. The researcher used a comparative study. Parametric test was used to test the difference in SO2 percent and evaluate the questionnaire in the two groups. The results showed after undergoing exercise, SO2 percent in participants was 94.60±0.55 for aerator masks and 96.60±0.55 for medical masks. The study also showed that there was no significant difference in SO2 percent of participants wearing aerator masks and medical masks. However, the decrease in oxygen saturation percent of participants wearing aerator masks experienced a lower decrease, 1.60±0.55 compared to medical masks of 2.00±1.00. On the other hand, wearing an aerator mask is better because it does not prevent maximum performance, better comfort, the mask material feels better on the skin, does not experience difficulties breathable, and suitable for exercise. An aerator mask is a mask with an adequate supply of oxygen so that every breath is maintained even when used during sports activities.